3D LIF/Mie planar droplet sizing in IC engine sprays using single-droplet calibration data - Kögl, Matthias; Mishra, Yogeshwar Nath; Hofbeck, Bernhard; Baderschneider, Kevin; Huber, Franz; Pracht, Jonas; Berrocal, Edouard; Zigan, Lars; Will, Stefan (ICLASS 2018: 14TH INTERNATIONAL CONFERENCE ON LIQUID ATOMIZATION & SPRAY SYSTEMS, 2018)

3D LIF/Mie planar droplet sizing in IC engine sprays using single-droplet calibration data - Kögl, Matthias; Mishra, Yogeshwar Nath; Hofbeck, Bernhard; Baderschneider, Kevin; Huber, Franz; Pracht, Jonas; Berrocal, Edouard; Will, Stefan; Zigan, Lars (ICLASS 2018 - 14th International Conference on Liquid Atomization and Spray Systems, 2020)
This paper reports on the quantitative 2D and 3D droplet sizing based on the LIF/Mie ratio in ethanol DISI (Direct Injection Spark Ignition) sprays, where the required calibration is performed using quantitative micro and macro LIF/Mie ratio imaging of individual microdroplets. The droplets are generated from a monodisperse droplet generator in a diameter range from 16 µm to 60 µm. First, the liquid LIF (laser-induced fluorescence) and Mie scattered light (Mie) intensity from the dye-doped ethanol droplet illuminated by the 532 nm laser sheet are simultaneously recorded using a microscopic and a macroscopic imaging objective. The light intensity of the LIF and Mie optical signals are evaluated as a function of droplet diameters (d). The LIF and Mie intensity is found in a good agreement with volumetric (d3) and surface (d2) dependencies, respectively. Both micro and macro LIF/Mie intensity ratio show a linear dependence on d. The deduced calibration curve showing a correlation between LIF/Mie intensity ratio and droplet diameter is then used for the calibration of LIF/Mie ratio for 3D droplet size (Sauter Mean Diameter: SMD) in sprays. For 3D sizing, two-phase SLIPI-(Structured Laser Illumination Planar Imaging) based droplet sizing is applied in combination with laser sheet scanning for probing the spray in several two-dimensional (2D) slices. These 2D layers are combined together to reconstruct a quantitative 3D map of droplet SMD. Droplet SMD in the spray is found in the range between 10 µm and 50 µm.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Direct-injection spark ignition (DISI); Ethanol; Laser-induced fluorescence; Mie scattering; SLIPI

3D mapping of droplet Sauter mean diameter in sprays - Mishra, Yogeshwar Nath; Kögl, Matthias; Baderschneider, Kevin; Hofbeck, Bernhard; Berrocal, Edouard; Conrad, Chris; Will, Stefan; Zigan, Lars (Applied Optics, 2019)
In this study, we report on the three-dimensional (3D) characterization of a spray in terms of its droplet Sauter mean diameter (SMD) using the laser-induced fluorescence (LIF)/Mie ratio technique. The spray structure is analyzed for a multi-hole direct-injection spark ignition (DISI) injector. A calibration curve to convert the LIF/Mie ratio to droplet diameter is deduced using LIF/Mie imaging and analysis of single droplets generated by a droplet generator. The DISI spray investigated here is optically sectioned by means of two-phase structured laser illumination planar imaging to suppress the intensity of multiple light scattering from LIF and Mie images prior to their ratio. A series of calibrated LIF/Mie ratio images of spray is then recorded at several depths along the z direction following the light sheet scanning of the spray. The droplet SMD ranges from less than 5 mu m up to a maximum of 50 mu m in single-shot images. The averaged SMD results (1-30 mu m) obtained by using the calibration curve from the droplet generator are compared with measurement results from phase-Doppler anemometry. Finally, a 3D map is reconstructed from the successive 2D layers generated from spray scanning. The resulting 3D representation of the droplet SMD shows a non-symmetric spray structure produced by the studied multi-hole injector, which cannot be resolved by analyzing only one central plane. (C) 2019 Optical Society of America
CRIS-Team WoS Importer:2019-05-24

Analysis of ethanol and butanol DISI sprays using two-phase SLIPI droplet sizing - Kögl, Matthias; Hofbeck, Bernhard; Will, Stefan; Zigan, Lars (Applied Energy, 2018)

Analysis of LIF and Mie signals from single micrometric droplets for instantaneous droplet sizing in gasoline sprays - Kögl, Matthias; Baderschneider, Kevin; Hofbeck, Bernhard; Will, Stefan; Zigan, Lars (Proceedings 9th European Combustion Meeting (ECM 2019), 2019)

Analysis of LIF and Mie signals from single micrometric droplets for instantaneous droplet sizing in sprays - Kögl, Matthias; Hofbeck, Bernhard; Baderschneider, Kevin; Mishra, Yogeshwar Nath; Huber, Franz; Berrocal, Edouard; Will, Stefan; Zigan, Lars (Optics Express, 2018)

Analysis of the LIF/Mie Ratio from Individual Droplets for Planar Droplet Sizing: Application to Gasoline Fuels and Their Mixtures with Ethanol - Kögl, Matthias; Baderscheider, Kevin; Bauer, Florian; Hofbeck, Bernhard; Berrocal, Edouard; Will, Stefan; Zigan, Lars (Applied Sciences, 2019)
Keywords: laser-induced fluorescence; nile red; Mie scattering; gasoline; model fuel; ethanol

High-speed soot luminescence and volumetric extinction measurements for investigation of the sooting combustion of ethanol fuel blends in a DISI engine - Kögl, Matthias; Hofbeck, Bernhard; Zigan, Lars; Will, Stefan (8th European Combustion Meeting, Dubrovnik, 2017)

Improved instantaneous droplet sizing in automotive sprays using the LIF/Mie ratio and structured illumination - Kögl, Matthias; Baderschneider, Kevin; Mishra, Yogeshwar Nath; Hofbeck, Bernhard; Zigan, Lars; Will, Stefan (International Conference on Advanced Optical Technologies, 2019)

Influence of EGR and ethanol blending on soot formation in a DISI engine - Kögl, Matthias; Hofbeck, Bernhard; Will, Stefan; Zigan, Lars (International Symposium on Combustion 2018, 2018)

Investigation of soot formation and oxidation of ethanol and butanol fuel blends in a DISI engine at different exhaust gas recirculation rates - Kögl, Matthias; Hofbeck, Bernhard; Zigan, Lars; Will, Stefan (Applied Energy, 2018)
Keywords: Extinction; High-speed; Soot luminescence; Soot oxidation; Particle formation; Pool-fire

Untersuchung der Rußbildung und Rußoxidation von Ethanol- und Butanolgemischen in einem Transparentmotor mit Benzindirekteinspritzung - Kögl, Matthias; Hofbeck, Bernhard; Will, Stefan; Zigan, Lars (11. Tagung Einspritzung und Kraftstoffe 2018, 2019)
Die Arbeit beschreibt die Detektion des Rußvolumenbruchs im Brennraum eines optisch zugänglichen Motors mit Benzindirekteinspritzung mittels volumetrischer High-Speed-Extinktionsmesstechnik. Vorteilhaft an dieser Methode ist die Möglichkeit einer zyklusaufgelösten Detektion der Rußkonzentration (bzw. des Rußvolumenbruchs), so dass die Rußbildung und Oxidation als auch die zyklischen Schwankungen der Rußverteilung herausgearbeitet werden können. Als Modellkraftstoff wird Toliso genutzt, eine Kraftstoffmischung bestehend aus 65 Vol.-% Isooktan und 35 Vol.-% Toluol.<br

Volumetric high-speed soot volume fraction measurements within a DISI-engine for ethanol and butanol fuel blends at varying EGR-rates - Kögl, Matthias; Hofbeck, Bernhard; Will, Stefan; Zigan, Lars (Laser Diagnostics in Combustion Gordon Research Conference, 2017)